Depresión geriátrica y trastornos cognitivos - Dechent R., Claudia (Revista Hospital Clínico Universidad de Chile, 2008)
At the present, the depression constitutes one of the high-priority diseases in public health and frequently affects to the old people with chronic pathologies, mental deterioration and/or loss of functionality, causing suffering to the patient and family, as well as diminution in the functional capacity and worsening of the basic pathologies. The geriatric depression has symptoms that differentiate it from the depression of early onset, such as, less frequency of familiar antecedents and alterations of the personality, greater presence of psychotic and mental symptoms, greater association with cardiovascular risk factors and presence of comorbidities, as well as tendency to chronicity, delayed response to drugs, risk of relapses and/or of evolution to dementia. Given the important prevalence, the clinical course and the existence of subclinical symptoms of difficult detection, becomes necessary to incorporate to the daily practice, simple but effective tests of affective and mental evaluation with the purpose of to derive and/or to try, with pharmacological, rehabilitating and psychotherapeutic approaches.